LANGUAGE ACQUISITION: THE EFFORTS OF AFGHAN REFUGEES IN COMMUNICATING WITH LOCAL PEOPLE - Bustam, Sri Reski; Djamereng, Jumharia; Emmiyati, Nuri (Universitas Islam Negeri Sunan Gunung Djati, 2024)
Language acquisition is a process which is experienced by a child in acquiring a first and second language. It needs a natural setting of target language in order to convey and understand the message correctly. The research was designed as a qualitative study to describe the process of second language acquisition experienced by Afghan refugees living in Makassar City for 5 to 10 years. In addition to describing the language acquisition process for Bahasa Indonesia as a second language, the study also explored the factors influencing this process. The research took 10 Afghan refugees who were proficient in Bahasa Indonesia as participants. To gather data related to their language acquisition and the factors influencing it, the informants were interviewed. Observation was used to supplement and verify the data on Bahasa Indonesia acquisition from the interviews. Thus, the data were analysed based on Krashen's theory (1995) of acquisition learning and the factors that influenced the informants' language acquisition. The research revealed that the refugees in Makassar used various methods (self-learning, courses) to acquire Bahasa Indonesia. They progressed through the five stages of language acquisition. Internal (motivation, personality, aptitude) and external factors (learning situations, local interactions) influenced their learning. Despite challenges, they persevered by practicing with Indonesian neighbours.Keyword: language acquisition, Afghan refugees, efforts, interaction, local people